Digestive system for the re-design of performance assessment - E Farida; A R Wulan; R Solihat (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
In the 21st century this required an increase in student health literacy. Literacy of digestive health is important to be improved.Various efforts were made, one of them by using performance assessment for learning. The purpose of this study is to describe the use of re-design performance assessment to improve student health literacy. The research method used is descriptive method. Instrument used consisted of teacher questionnaire, student questionnaire, task, rubric and feedback mechanism. Health literacy is measured by 4 dimensions on the Partnership-21 Century Skills framework. The data were analysed descriptively. The results of the use of tasks, rubric and feedback mechanism obtained an increase in the fourth dimension of student health literacy.